Successful (?) therapy of hemolytic-uremic syndrome with factor H abnormality - Gerber, Angela; Kirchhoff-Moradpour, Antje H.; Obieglo, Silke; Brandis, Matthias; Kirschfink, Michael; Zipfel, Peter F.; Goodship, Judith A.; Zimmerhackl, Lothar B. (Pediatric nephrology, 2003)
We report a patient with continuously recurring hemolytic-uremic syndrome due to factor H deficiency. First at the age of 3 months he showed signs of hemolytic anemia, thrombocytopenia and renal insufficiency, often recurring concomitantly with respiratory tract infections, despite weekly to twice weekly plasma substitution (20 ml/kg body weight). Now at the age of 3.5 years glomerular filtration rate is approximately 50 ml/min/1.73 m(2) and psychomotoric development is normal. Since factor H is mainly synthesized in the liver, hepatic transplantation has been proposed as curative treatment. Before justification of liver transplantation as the ultimate treatment for these patients, an international registry should be developed to optimize and standardize therapeutic alternatives.
Gesehen am 15.02.2021